Modelo em circuito elétrico equivalente para uma bateria single cell de sódio-cloreto de níquel - Marcondes, Alexandre (2019)
With an ever-increasing demand for energy among the world, growing contribution of renewable energy sources in the energy matrix, and the constant rise of hybrid and electric vehicles production levels, research and development of energy storage area seeks more attention. Energy storage come as an allied in the issue of intermittent generation of renewable energy sources and is essential for electric powered vehicles. The sodium-nickel chloride battery sits as a good alternative for energy storage, with long lifetime and big theoretical energy density. Battery modelling is a constant in the technology development: used to simulate battery behavior – electrical circuit simulations – as well as in battery management systems to predict states of the battery. This work uses empirical tests in order to obtain an equivalent electrical circuit model to predict the current-voltage behavior of a single cell sodium-nickel chloride battery. With the “pulse discharge voltage” measurements, the model parameters were estimated using the non-linear least squares method for different levels of state of charge. At the results the third order Thevenin model achieved the best accuracy, meanwhile the first order model achieved the worst results. The simulation results show that as the model order increase, more accurate the model will be, but the computational cost for the parameter extraction and the simulation will increase as well.